Specific hypertensive disorders of pregnancy in a tertiary hospital in northeastern brazil epidemiological profile - Zélia Maria de Sousa Araújo Santos; Rithianne Frota Carneiro; Geraldo Bezerra da Silva Junior; Janaína da Silva Feitoza Palácio; Jennara Cândido do Nascimento (Universidade de Fortaleza, 2015)
Objective: To describe the epidemiological profile of women admitted to a tertiary hospital in Northeastern Brazil with Hypertensive Disorders of Pregnancy (HDP). Methods: A retrospective cross-sectional study was carried out at the Hospital Geral César Cals (César Cals General Hospital), a tertiary care center of the Sistema Único de Saúde - SUS (Brazil's National Health System) in Fortaleza, Ceará, Brazil. The study included 1,865 pregnant women admitted with HDP from January 2006 to December 2013 regardless of age, education, marital status, place of birth, place of residence and outcome (discharge, death and ongoing pregnancy). Results: Pregnant women were predominantly aged 17-35 years (n=1484, 79.6%), mixed-race (n=1464, 78.5%), single (n= 775, 41.6%), housewives (n=1269, 68.0%), lived in Fortaleza (n=1198, 64.3%) and had complete elementary education (n=766, 41%). Overweight (n= 1408, 75.4%), first pregnancy (n=827, 44.3%) and multiparity (n=686, 36.7%) were the main risk factors for HDP. Regarding fetal status, 30.9% (n=576) were preterm. The main HDP complications were: HELLP syndrome (n=60, 3.2%), bleeding disorders (n=15, 0.8%) and acute respiratory failure (n=13, 0.6%). Conclusion: The pregnant women assessed presented risk factors for HDP, reinforcing the idea that the health status and the disease and health process are directly influenced by socioeconomic and demographic characteristics of the population.